PEMANFAATAN LIMBAH KULIT ANGGUR LOKAL DALAM PEMBUATAN JELLY DRINK - Setiawati, Ira; Ekawati, I Gusti Ayu; Sri Wiadnyani, AA Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2017)
The objective of this research was to observe the effect of grape skin waste on the characteristic of jelly drink and to determine the appropiate treatment that produces jelly drink with the best characteristics. Data was analyzed using completely randomized design (CRD) with five levels such as 100g of grape skin waste, 200g of grape skin waste, 300g of grape skin waste, 400g of grape skin waste, and 500g of grape skin waste. Data were analyzed with analysis of variance and continued with Duncan’s Multiple Range Test. The result showed that the effect of each treatment gave significant effect to total phenol, vitamin C, anthocyanin, antioxidant activity and gave significant effect to characteristic of color, aroma, taste, and overall acceptance. The best treatment to produce jelly drink was 500g of grape skin waste, that gave average value total phenol 83.64 mg GAE/100g, vitamin C 35.92 mg/100g, anthocyanin 3.90 mg/100g, IC50 3872.36 ppm, color dark purple, aroma very typical grape, and texture slightly chewy, taste and overall acceptance was liked.
Keywords: grape skin, jelly drink, waste